Demographic Factors Influencing Academic Procrastination among Postgraduate Students - Salihu, Nurudeen Oganija; Abdulkareem, Habibat Bolanle (Jurnal Pedagogi dan Pembelajaran, 2024)
Academic procrastination is a global problem that mar the development of individuals, especially in the area of education. This study investigates the relationship between demographic factors and academic procrastination among postgraduate students. Quantitative research approach, descriptive design of the survey type was considered for this study. Data were collected from 325 postgraduate students across various faculties and postgraduate programs. Simple percentage count and t-test was used to analyze the data. The majority of respondents were male, aged between 25 and 40 years, and enrolled in Master's programs. Three hypotheses were formulated and tested using a t-test statistical method at a significance level of 0.05. Hypothesis one, which examined the influence of gender on academic procrastination, found no significant difference between male and female students. Similarly, hypothesis two, exploring the impact of age on academic procrastination, revealed no significant difference between younger (25-40 years) and older (41 years and above) students. However, hypothesis three, which investigated the relationship between employment status and academic procrastination, showed a significant difference between employed and unemployed students, with employed students exhibiting lower levels of procrastination. These findings suggest that while gender and age may not significantly influence academic procrastination among postgraduate students, employment status does play a significant role.